Aggression behavior and substance use among immigrant children: Mediating effect of antisocial attitudes. Issue 1 (2nd January 2017) - Small, Eusebius; Kim, Youn Kyoung; Mengo, Cecilia
ABSTRACT: In 2010, approximately one out of four youths in the United States were immigrant children. Hispanics and Asians comprised the largest groups (58% and 16%), respectively. Today, the Hispanic population is the largest ethnic minority in the United States (15%) and is a majority of the U.S. foreign-born population (47%). While immigration is a positive process for most immigrants, resettlement into a new country has challenges, including acculturation adjustments. Youth engage in risky behaviors such as substance use and antisocial behaviors. For immigrant youth with limited supportive opportunities, however, the acculturation process can be difficult. Stress, alienation, and stigma often manifest and cause behavioral problems, including aggression. This pilot study examines the mediating effect of antisocial attitudes using sociocultural, developmental, and environmental factors to understand Hispanic youth problem behaviors. We sampled 136 youths, ages 6–12, from predominantly Hispanic elementary schools in the southwestern United States to ascertain the role of aggression and antisocial behavior in substance use attitudes. The results show significant differences in aggression, antisocial attitudes, and substance use according to (1) age, (2) years in the United States, (3) English level, and (4) relationship with mother. Aggression significantly predicted antisocial attitudes and substance use, with antisocial attitudes having a mediating effect on the relationship between aggression and substance use. In developing social service programs to prevent substance use among children from immigrant families, social work educators and practitioners may consider addressing the role of aggression in Hispanic adolescents' future behavior.